Post-burns persistent inflammation leads to kidney PANoptosis with Caspases pathway activation - Guang Yang; Minghui Wang; Mulan Qahar; Jinqing He; Zhiwei Lai; Sanmu Li; Dehua He; Xuefei Yan; Zuying Xiong; Zibo Xiong; Thu H. Le (Heliyon)
Background: There is higher prevalence of chronic kidney disease (CKD) in burn patients after hospital discharge; however, the cause remains unclear. This study aimed to investigate the lasting impacts of severe burns on the kidneys and to explore potential treatments. Methods: The study examined the effects of burning on healthy mice and adenine-induced CKD mice. Subsequently, the investigation focused on assessing the effects of activated macrophages on podocytes. Finally, the study evaluated the effectiveness of dexamethasone in mitigating the impacts of burns on the kidneys. Results: In healthy mice, burns caused only subclinical signs in the kidneys. However, in the CKD group, burns not only reduced kidney function, but also aggravated kidney injuries, apoptosis, and inflammation. Moreover, the expression of Caspase-1 and -3 signalings was significantly increased in all mice after burns. Electron microscopy revealed that burns exacerbated glomerular injury in the CKD group, including podocyte injury, cell membrane blebbing, and rupture. Furthermore, polarized M1 macrophages led to increased MPC5 podocyte death. Following dexamethasone intervention, kidney function and injuries were alleviated in CKD mice. Conclusions: Severe burns can trigger PANoptosis by activating inflammation-induced Caspase-dependent pathways, which can lead to kidney injury in mice. This impairment is exacerbated in the CKD group. However, the administration of dexamethasone can effectively ameliorate kidney injury. These findings have significant implications for predicting the prognosis of kidney function in burn patients and offer a potential therapeutic approach.